(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The current study was designed to investigate the therapeutic role of the water extract of leaves of ginkgo biloba plant against the acute poisoning of the nervous system caused by exposure to mercury. Experimental animals were divided into four groups. The first group was treated as a control group treated with physiological saline solution. The second group was given mercury chloride at 0.12 mg / kg . bw for seven days. The third group was given mercury chloride orally at 0.12 mg / Kg for five days and then injected under the peritoneal membrane with water extract for leaves of ginkgo plant for 25 days at a concentration of 250 mg / kg / day, while The fourth group gave mercury chloride for five days and then injected with the water extract of the leaves of the ginkgo plant at a concentration of 500 mg / kg / day under the peritoneal membrane. All groups were treated daily according to prescribed doses and 24 hours after the last given dose, the animals were explained and the study criteria were met. Mercury treatment caused obvious tissue changes in brain tissue. The treatment with water extract of leaves of the ginkgo plant led to improvement in brain cells and tissues.